Commodity Fetishism in Kazuo Ishiguro’s A Pale View of Hills (Journal of Musikot Campus, 2025)
Kazuo Ishiguro’s A Pale View of Hills (1982), a Nobel Prize-winning novel, explores how human relationships become transactional, eroding genuine interpersonal and familial bonds. This study examines characters' alienation through Karl Marx’s critique of capitalist society and the concept of the commodification of human relations, illustrating how marriage and other personal connections shift from emotional to economic exchange. As relationships become entangled in consumer culture, cultural and personal identities are lost, leaving individuals traumatized in the aftermath of the Second World War. The characters Etsuko, Keiko, Sachiko, Mariko fail to form authentic relationships with other members due to the pervasive influence of western capitalist interactions, leading to alienation and, ultimately, the suicide of Keiko. Commodity fetishism weakens individuals and strengthens monetary value, giving additional importance to the exchange value. This vulnerability smashes the complete harmony of the social relations. This article argues that socio-economic pressures reshape personal and social connections, demonstrating that commodified relationships fracture individual and cultural identities in post-war Nagasaki of Japan. It infers the novel as a critique of capitalist society.